Aryl Hydrocarbon Receptor: From Homeostasis to Tumor Progression - Rejano-Gordillo, Claudia; Ordiales-Talavero, Ana; Nacarino-Palma, Ana; Merino, Jaime M.; González-Rico, Francisco J.; Fernández-Salguero, Pedro M. (Frontiers in Cell and Developmental Biology, 2022)
Transcription factor aryl hydrocarbon receptor (AHR) has emerged as one of the main regulators involved both in different homeostatic cell functions and tumor progression. Being a member of the family of basic-helix-loop-helix (bHLH) transcriptional regulators, this intracellular receptor has become a key member in differentiation, pluripotency, chromatin dynamics and cell reprogramming processes, with plenty of new targets identified in the last decade. Besides this role in tissue homeostasis, one enthralling feature of AHR is its capacity of acting as an oncogene or tumor suppressor depending on the specific organ, tissue and cell type. Together with its well-known modulation of cell adhesion and migration in a cell-type specific manner in epithelial-mesenchymal transition (EMT), this duality has also contributed to the arise of its clinical interest, highlighting a new potential as therapeutic tool, diagnosis and prognosis marker. Therefore, a deregulation of AHR-controlled pathways may have a causal role in contributing to physiological and homeostatic failures, tumor progression and dissemination. With that firmly in mind, this review will address the remarkable capability of AHR to exert a different function influenced by the phenotype of the target cell and its potential consequences.